PENGARUH KOMPONEN LAPORAN ARUS KAS TERHADAP RETURN SAHAM DENGAN CURRENT RATIO SEBAGAI VARIABEL MODERASI - Dirgayusa, I Gede Putu; Suardikha, I Made Sadha (E-Jurnal Akuntansi, 2017)
This study aims to determine the effect of each component of the cash flow statement and the current ratio on stock returns and the ability of the current ratio as the moderating to influence the operating cash flow to stock return. Population in this study are all manufacturing companies listed on the Indonesian stock exchange from 2010 to 2014 period, which amount to 130 companies. The sampling method is based on the nonprobability sampling approach using purposive sampling method, that was selected as many as 63 companies that meet the criteria of purposive sampling that has been determined. Hypothesis test results shows that the investment cash flow and financing cash flow has negative effect on stock returns, while operating cash flow and the current ratio does not affect the return. Moderation test shows that the current ratio is unable to moderate the effect of operating cash flow to stock return.
Keywords: stock return, component of cash flows, current ratio